Quantitative evaluation of intensity fidelity of super-resolution reconstruction for structured illumination microscopy - Yujun Tang; Linbo Wang; Gang Wen; Hui Li (Journal of Innovative Optical Health Sciences)
Super-resolution structured illumination microscopy (SR-SIM) relies heavily on post-processing reconstruction to obtain high-quality SR images from raw data. Although many SIM reconstruction algorithms have been developed to recover fine cellular structures with high fidelity even from the noisy data, whether the pixel intensities of reconstructed SR images are still proportional to the original fluorescence intensity has been less explored. The linearity between the intensity before and after reconstruction is defined as the intensity fidelity. Here, we proposed a method to evaluate the reconstructed SR image intensity fidelity at different spatial frequencies. With the proposed metric, we systematically investigated the impact of the key factors on the intensity fidelity in the standard Wiener-SIM reconstructions with simulated data, then evaluated the intensity fidelity of the SR images reconstructed by representative open-source packages. Our work provides a reference for SR-SIM image intensity fidelity improvement.